In Vitro Cytotoxicity of Fluorinated Quaternary Ammonium Salts in Colorectal Cancer Cells and In Silico Pharmacology - Adriana Milena Olarte Aponte; Victoria Ospina; Sergio A. Pulido; Luz Amalia Ríos-Vásquez; Luz Adriana Betancur Jaramillo; Carlos Mario Muñetón Peña; Rogelio Ocampo-Cardona; Sara M. Robledo (Advances in Pharmacological and Pharmaceutical Sciences)
Colorectal cancer (CRC) is a multifactorial disease driven by genetic and epigenetic alterations that modulate specific metabolic pathways. Despite the availability of effective treatments like 5-fluorouracil (5-FU), pharmacological therapy for CRC still faces significant challenges, including drug resistance, toxicity, and limited specificity. Therefore, discovering new compounds remains critical to overcoming these barriers and expanding treatment options. This study evaluated the cytotoxicity of fluorinated quaternary ammonium salts (FQAS) library in CRC-derived cell lines with premetastatic and metastatic phenotypes. The genetic and epigenetic background of the CRC cell lines and the selectivity of cytotoxicity compared to nontumor cells and between different CRC stages were also assessed. Additionally, the in silico pharmacological properties of these FQASs were analyzed. Results showed that FQASs 9–14 exhibited significant cytotoxic activity against both premetastatic and metastatic CRC cell lines, with FQASs 9, 13, and 14 displaying selective toxicity toward CRC cells over normal murine colorectal cells. However, in silico studies indicated poor oral bioavailability for these compounds, suggesting that an injection-based delivery route may be more effective for targeting CRC cells. In conclusion, CF3-containing FQASs are promising therapeutic candidates for CRC treatment.